A case report: X-linked dystrophin gene mutation causing severe isolated dilated cardiomyopathy. Issue 2 (3rd May 2019) - Lester, Geoffrey; Femia, Giuseppe; Ayer, Julian; Puranik, Rajesh
Abstract: Background : X-linked dilated cardiomyopathy (XLDCM) is a rare but rapidly progressive cardiomyopathy caused by dystrophin gene mutation. Mutations are more often associated with Duchenne and Becker Muscular Dystrophy, which are characterized by skeletal muscle weakness or limb girdle dystrophy. However, patients with isolated XLDCM have normal skeletal muscle but complete dystrophin loss in cardiac muscle resulting in isolated myocardial involvement without overt signs of skeletal myopathy. Case summary : A previously well 16-year-old boy developed sudden onset dense left-sided weakness and facial droop. Computed tomography (CT) angiography and CT brain showed an occluded right internal carotid artery extending to the right middle cerebral artery. He underwent successful endovascular clot retrieval but developed frank pulmonary oedema and cardiogenic shock requiring inotropic support and intubation. Transthoracic echocardiography demonstrated severe left ventricular (LV) cardiomyopathy and an apical thrombus. Subsequent cardiac magnetic resonance (CMR) imaging confirmed the LV parameters and diffuse late gadolinium enhancement. Despite absence of skeletal manifestations, subsequent genetic testing revealed an X-linked dystrophin gene mutation [c.31+G>T (IVS1G>T)]. He was commenced on empirical heart failure therapy and underwent successful cardiac transplantation. Discussion : X-linked dilated cardiomyopathy is a rare, rapidly progressing cardiomyopathy. Patients show normal skeletal muscle dystrophin but absent expression in cardiac muscle, resulting fibrosis, and atrophy. About 20% of affected young males have significantly reduced survival and thus the diagnosis must be considered in cases of idiopathic cardiomyopathy with CMR and genetic testing key to the diagnosis. Whilst evidence exists for empirical heart failure medications, cardiac transplantation remains the definitive treatment.